Towards point-of-care HIV testing: Terahertz PCF sensor integration and miniaturization - Most. Momtahina Bani; Md. Mynuddin; Khalid Sifulla Noor; A. H. M. Iftekharul Ferdous; Md. Safiul Islam (PLoS ONE, 2025)
The Human Immunodeficiency Virus, or HIV, is a retrovirus which aims at CD4 cells in particular to destroy the body’s natural defenses along with impair its capacity for fighting off illness plus ailments. In this circumstance we suggested a Photonic Crystal Fiber (PCF) sensor for detection of this lethal virus. Our intended sensor exhibits Max Relative Sensitivity (RS) 95.2% & 95% for x & y axis correspondingly when f = 3.0 THz. It also impresses us with minimal Confinement Loss (CL) of 1.06 × 10−7 & 2.04 × 10-7dB/m plus Effective Material Loss (EML) of 0.0078 & 0.0110 cm−1 in that order for x & y axis. Initial detection alongside prompt cures for HIV are made feasible by the remarkable efficacy of PCF biosensor observations in this regard. PCF gadgets offer rapid, non-invasive medical diagnosis, which simplifies the need for further evaluation & allows for an assessment of a condition’s progression as it progresses. Precise assessment may be beneficial when investigating advancements that improve worldwide identification and therapeutic choices. It is possible that the rapid identification of these harmful microbes was made possible by the remarkable identifying ability provided by the new PCF. In conclusion, healthcare offers a plethora of opportunity.